NANOCRISTAIS DE CELULOSE COMO REFORÇO EFICIENTE EM COMPÓSITOS POLIMÉRICOS UTILIZANDO MONÔMERO DE ESTIRENO COMO AGENTE COMPATIBILIZANTE - Maradini, Grazielle da Silva (2020)
The application of cellulose nanocrystals (CNC) as reinforcement in the development of composite materials has attracted the interest of the academic community and several industrial sectors, due to their physical and mechanical properties, in addition to